Architecture and Key Capabilities of Management System of Smart Home Device - Tao Guo; Jianting Han; Xiaoling Yang (Dianxin kexue)
Firstly,the operator's challenges of developing smart home system in the new situation were analyzed,then the key demands of smart home management system were studied.Finally,the platform framework,function framework and implementation suggestion of smart home management system was proposed.